The Relationship Between Social Vulnerability and COVID-19 Incidence Among Louisiana Census Tracts - Biggs, Erin N.; Maloney, Patrick M.; Rung, Ariane L.; Peters, Edward S.; Robinson, William T. (Frontiers in Public Health, 2021)
Objective: To examine the association between the Centers for Disease Control and Prevention (CDC)’s Social Vulnerability Index (SVI) and COVID-19 incidence among Louisiana census tracts. Methods: An ecological study comparing the CDC SVI and census tract-level COVID-19 case counts was conducted. Choropleth maps were used to identify census tracts with high levels of both social vulnerability and COVID-19 incidence. Negative binomial regression was used to compare the relationship between overall CDC SVI percentile and its four sub-themes and COVID-19 incidence, adjusting for population density. Results: In a crude stratified analysis, all four CDC SVI sub-themes were significantly associated with COVID-19 incidence. Census tracts with higher levels of social vulnerability were associated with higher COVID-19 incidence after adjusting for population density (adjusted RR: 1.54, 95% CI: 1.42-1.67). Conclusions: The results of this study indicate that increased social vulnerability is linked with COVID-19 incidence. Additional resources should be allocated to areas of increased social disadvantage to reduce the incidence of COVID-19 in vulnerable populations.